2013
DOI: 10.1007/s13577-013-0075-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of dedifferentiated fat cells for periodontal tissue regeneration

Abstract: Periodontal diseases result from inflammation by bacterial infection in plaques, leading to tooth loss. However, regenerative approaches with periodontal tissue regeneration by guided tissue regeneration and enamel matrix derivative are not yet well established. Tissue regeneration requires three factors: cells, scaffold, and growth factors. Dedifferentiated fat cells (DFATs) are pluripotent with the same differentiation capacities as mesenchymal stem cells (MSCs). Access to MSCs is limited, whereas donor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
2
18
0
1
Order By: Relevance
“…Newly formed alveolar bone was observed by HE staining after 4 weeks of cell transplantation. Small amounts of newly formed cementum‐like structures were also observed on the exposed root surface (Sugawara & Sato, ). Akita et al.…”
Section: Dfat Cells For Oral and Maxillofacial Tissue Engineering—in mentioning
confidence: 99%
See 1 more Smart Citation
“…Newly formed alveolar bone was observed by HE staining after 4 weeks of cell transplantation. Small amounts of newly formed cementum‐like structures were also observed on the exposed root surface (Sugawara & Sato, ). Akita et al.…”
Section: Dfat Cells For Oral and Maxillofacial Tissue Engineering—in mentioning
confidence: 99%
“…Newly formed alveolar bone was observed by HE staining after 4 weeks of cell transplantation. Small amounts of newly formed cementum-like structures were also observed on the exposed root surface (Sugawara & Sato, 2014 T A B L E 1 Expression pattern of CD antigens in human Dedifferentiated Fat (DFAT) cells and in other types of stem cells alveolar bone than the ASCs+PLGA or PLGA alone groups . Kikuta and colleagues seeded DFAT cells in β-tricalcium phosphate (β-TCP)/collagen I sponges and cultured in OIM for 2 weeks to form tissue-engineered bone (TEB).…”
Section: Periodontal Tissue Regenerationmentioning
confidence: 99%
“…According to a systematic review, PDL-derived cells showed a favorable effect on new PDL formation, although there was no statistically significant difference between PDL-derived or Bone marrow derived stem cells [48]. Other cell types like DPSC [49], GMSC [50], DFAT [51], SHED [52] have also been able to successfully regenerate periodontal tissue.…”
Section: Periodontal Complexmentioning
confidence: 99%
“…DFAT cells have emerged as a potential cell source for regenerative medicine because of their transdifferentiation capability and similarity to ASCs and bone marrow MSCs [75][76][77] . Multiple studies have demonstrated differentiation of DFAT cells into multiple lineages including adipogenic, osteogenic, chondrogenic, myogenic, angiogenic and neurogenic lineages (Figure 3).…”
Section: Differentiation Potential Of Dfat Cellsmentioning
confidence: 99%